Organizational Assimilation of Innovations: A Multilevel Contextual Analysis - Meyer, Alan D.; Goes, James B. (Academy of Management Journal, 1988)
This study examined the assimilation of innovations into organizations, a process unfolding in a series of decisions to evaluate, adopt, and implement new technologies. Assimilation was conceptualized as a nine-step process and measured by tracking 300 potential adoptions through organizations during a six-year period. We advance a model suggesting that organizational assimilation of technological innovations is determined by three classes of antecedents: contextual attributes, innovation attributes, and attributes arising from the interaction of contexts and innovations.